Volatility Matters: Taylor Rules and Capital Accumulation - Massimiliano Marzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
The operational performance of a set of simple monetary pol- icy rules à la Taylor in a model with capital accumulation and nominal and real rigidities is discussed with a special emphasis on the volatility of output, nominal rate and in.ation rate. Within an enriched modelling framework it is shown that output targeting plays a more crucial role than what has been assessed in the current literature for models without capital accumulation. In fact, with a small value of the output targeting coefficient, monetary authority is not completely successfull in stabilizing the volatility of output, nominal rate and inflation rate only by acting on inflation targeting. Moreover, a too strong concerns towards inflation relatively to output translates into a lower ability to control inflation volatility, together with a strong policy reaction with respect to an exogenous shock hitting the economy. Im- pulse response analysis shows that the risk of an excessive concerns towards inflation might end up in counterproductive results on output, after a positive technological shock. The model also shows a better internal propagation mechanism than what has been previously showed. Finally, the results show that it is no longer possible to miss capital accumulation in modelling monetary policy analyses and calls for further generalizations of the existing modelling framework.
Keywords: 330; Geldpolitik; Regelbindung versus Diskretion; Taylor-Regel; Investition; Volatilität; Inflation; Theorie; USA